New Trends in Recycled Aggregate Concrete - de Brito, Jorge (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book is the result of a Special Issue published in Applied Sciences, entitled "New Trends in Recycled Aggregate Concrete"". It identifies emerging research areas within the field of recycled aggregate concrete and contributes to the increased use of this eco-efficient material.Its contents are organised in the following sections: Upscaling the use of recycled aggregate concrete in structural design; Large scale applications of recycled aggregate concrete; Long-term behaviour of recycled aggregate concrete; Performance of recycled aggregate concrete in very aggressive environments; Reliability of recycled aggregate concrete structures; Life cycle assessment of recycled aggregate concrete; New applications of recycled aggregate concrete.